Dopamine receptor subtype 2 expression profile in nonfunctioning pituitary adenomas and in vivo response to cabergoline therapy. (8th January 2015) - Vieira Neto, Leonardo; Wildemberg, Luiz Eduardo; Moraes, Aline B.; Colli, Leandro M.; Kasuki, Leandro; Marques, Nelma Verônica; Gasparetto, Emerson L.; de Castro, Margaret; Takiya, Christina Maeda; Gadelha, Mônica R.
Summary Objectives To determine the dopamine receptor subtype 2 (DR2) mRNA levels and protein expression and to evaluate the effect of adjuvant cabergoline therapy on tumour volume (TV) in patients with postoperative residual nonfunctioning pituitary adenoma (NFPA). Methods The mRNA expression was quantified by real‐time RT‐PCR (TaqMan®), and protein expression was evaluated by immunohistochemistry. Tumours were classified according to the percentage of immunostained cells for DR2 as scores 1 (<50% of stained cells) or 2 (≥50%). Cabergoline was started at least 6 months after surgery in nine patients with residual tumours (3 mg/week). The cabergoline effect was prospectively evaluated by magnetic resonance imaging using three‐dimensional volume calculation. TV reduction >25% was considered significant. Results The DR2 mRNA expression was variable but was observed in 100% of the samples (N = 20). DR2 protein expression was also observed in all the tumours (N = 34). Twenty‐nine tumours (85%) were classified as score 2. The median DR2 mRNA expression was higher in the tumours classified as score 2 compared with score 1 (P = 0·007). TV reduction with cabergoline therapy was observed in 67% of the patients (6/9). The median TV before and after 6 months of treatment was 1·90 cm3 (0·61–8·74) and 1·69 cm3 (0·36–4·20) [P = 0·02], respectively. Conclusion In conclusion, DR2 is expressed in all adenomas and the majority of the patients in this study displayed tumour shrinkage on cabergoline (CAB) therapy. Thus, CAB might be useful in adjuvant therapy in NFPA patients with residual tumours after surgery.